IPOM PLUS – AN EFFECTIVE METHOD IN TREATMENT OF VENTRAL HERNIA - Mitevski, A; Antovic S; Markov P (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University, Skopje, 2020)
ABSTRACT Introduction: Abdominal wall surgery for ventral hernia is one of the commonest procedures performed by surgeons. Hernias that occur after previous abdominal surgery - incisional hernias - appear in 11% to 20% of the cases, and the recurrence of ventral hernia is related to the presence of abdominal rectus muscle diastasis. Case: A patient who had two previous operations for ventral hernia with prosthesis was admitted. Hernia bulging and partially reducing content of the hernia sac when pressure applied was present. Intraoperative, a recurrent hernia was observed and pseudohernia – bulging out of the previous implanted prosthesis was noted, cephalic from the clinically diagnosed defect. Also a rectus muscle diastasis was present caudally. Discussion: The laparoscopic IPOM repair is associated to a high incidence of post-operative bulging or eventration of mesh, seromas, recurrences and non-restoration of abdominal muscle function. To overcome these problems, sutured closure of the defect in the fascia with intra-peritoneal mesh reinforcement has been described, known as the IPOM plus repair. This repair is the recommended procedure in the guideline of International Endohernia Society. Conclusion: In patients who are presented with diastasis of the abdominal rectus muscles in addition to the ventral hernia, plication of the diastasis can be done in order to help support of the ventral hernia and improve outcomes or can be sutured with transfascial non-absorbable single sutures along the diastasis. It brings considerable esthetic advantages and reduces the recurrence of hernias.
Keywords: IPOM plus; laparoscopic ventral hernia repair; mesh repair; rectalis muscle diastasis; ventral hernia